2011
DOI: 10.1097/sap.0b013e3181fc0507
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue

Abstract: Human fibrin sealant is an effective chondrocyte carrier and retains viable cells. Treatment of a nonarticular critical-size defect with resting zone chondrocytes embedded in a fibrin glue polymer demonstrates tissue healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has been widely used in many surgical disciplines including cranioplasty [12], spine surgery [13,14], and maxillofacial surgery [10,15,16]. Beside its hemostatic capabilities, FG has been employed as scaffolds for bone and cartilage tissue engineering [17][18][19]. It has been studied in vitro studies that the addition of fibrin network to collagen sponge increased the osteoblast differentiation in a dose-dependent way, suggesting that these materials may favor bone repair [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in many surgical disciplines including cranioplasty [12], spine surgery [13,14], and maxillofacial surgery [10,15,16]. Beside its hemostatic capabilities, FG has been employed as scaffolds for bone and cartilage tissue engineering [17][18][19]. It has been studied in vitro studies that the addition of fibrin network to collagen sponge increased the osteoblast differentiation in a dose-dependent way, suggesting that these materials may favor bone repair [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies showed reproducible cartilage formation in the defect of rat xiphoid. 28 - 30 They also showed that the formation of neocartilage in rat xiphoid was increased with fibroblast growth factor-2 in the absence of exogenous chondrocytes. 30 Since xiphoid cartilage in mice is subcutaneous, it allows for easy access; only limited surgical exposure is required, and the placement of the tissue allows for the application of consistent and quantifiable mechanical injury.…”
Section: Introductionmentioning
confidence: 94%